Nitroaspirin Corrects Immune Dysfunction in Tumor-Bearing Hosts and Promotes Tumor Eradication by Cancer Vaccination - De Santo, Carmela; Serafini, Paolo; Marigo, Ilaria; Dolcetti, Luigi; Bolla, Manlio; Del Soldato, Piero; Melani, Cecilia; Guiducci, Cristiana; Colombo, Mario P.; Iezzi, Manuela; Musiani, Piero; Zanovello, Paola; et al. (Proceedings of the National Academy of Sciences - PNAS, 2005)
Active suppression of tumor-specific T lymphocytes can limit the immune-mediated destruction of cancer cells. Of the various strategies used by tumors to counteract immune attacks, myeloid suppressors recruited by growing cancers are particularly efficient, often resulting in the induction of systemic T lymphocyte dysfunction. We have previously shown that the mechanism by which myeloid cells from tumor-bearing hosts block immune defense strategies involves two enzymes that metabolize L-arginine: arginase and nitric oxide (NO) synthase. NO-releasing aspirin is a classic aspirin molecule covalently linked to a NO donor group. NO aspirin does not possess direct antitumor activity. However, by interfering with the inhibitory enzymatic activities of myeloid cells, orally administered NO aspirin normalized the immune status of tumor-bearing hosts, increased the number and function of tumor-antigen-specific T lymphocytes, and enhanced the preventive and therapeutic effectiveness of the antitumor immunity elicited by cancer vaccination. Because cancer vaccines and NO aspirin are currently being investigated in independent phase I/II clinical trials, these findings offer a rationale to combine these treatments in subjects with advanced neoplastic diseases.